Spondylodiscitis Occurring after Diagnostic Lumbar Puncture: A Case Report - Mehmet Sabri Gürbüz; Mehmet Zafer Berkman (Case Reports in Infectious Diseases)
Spondylodiscitis is a rare disease which is generally seen after long-term epidural catheterization. However, spondylidiscitis developing after diagnostic lumbar puncture is very rare. Early diagnosis has a crucial role in the management of the disease and inclines the morbidity rates. However, the diagnosis is often delayed due to the rarity and insidious onset of the disease usually presenting with low back pain which has a high frequency in the society. If it is diagnosed early before development of an abscess requiring surgery or neurological deficit, it responds to antimicrobial therapy quite well. We report 66-year-old male case of spondylodiscitis developing after diagnostic lumbar puncture. The patient was treated with antimicrobial therapy. After antimicrobial therapy, findings of spondylodiscitis were completely resolved and no recurrence was seen in the period of 9-month followup.